Apoptotic-like programed cell death in fungi: the benefits in filamentous species - Shlezinger, Neta; Goldfinger, Nir; Sharon, Amir (Frontiers in Oncology, 2012)
Studies conducted in the early 1990's showed for the first time that Saccahromyces cerevisiae can undergo cell death with hallmarks of animal apoptosis. These findings came as a surprise, since suicide machinery was unexpected in unicellular organisms. Today, apoptosis in yeast is well documented. Apoptotic death of yeast cells has been described under various conditions and S. cerevisiae homologues of human apoptotic genes have been identified and characterized. These studies also revealed fundamental differences between yeast and animal apoptosis; in S. cerevisiae apoptosis is mainly associated with ageing and stress adaptation, unlike animal apoptosis, which is essential for proper development. Further, many apoptosis regulatory genes are either missing, or highly divergent in S. cerevisiae. Therefore, in this review we will use the term apoptosis-like programmed cell death (PCD) instead of apoptosis. Despite these significant differences, S. cerevisiae has been instrumental in promoting the study of heterologous apoptotic proteins, particularly from human. Work in fungi other than S. cerevisiae revealed differences in the manifestation of PCD in single cell (yeasts) and multi-cellular (filamentous) species. Such differences may reflect the higher complexity level of filamentous species, and hence the involvement of PCD in a wider range of processes and life styles. It is also expected that differences might be found in the apoptosis apparatus of yeast and filamentous species. In this review we focus on aspects of PCD that are unique or can be better studied in filamentous species. We will highlight the similarities and differences of the PCD machinery between yeast and filamentous species and show the value of using S. cerevisiae along with filamentous species to study apoptosis.